Evolution of chloroplast J proteins. - Chi-Chou Chiu; Lih-Jen Chen; Pai-Hsiang Su; Hsou-min Li (PLoS ONE, 2013)
Hsp70 chaperones are involved in multiple biological processes and are recruited to specific processes by designated J domain-containing cochaperones, or J proteins. To understand the evolution and functions of chloroplast Hsp70s and J proteins, we identified the Arabidopsis chloroplast J protein constituency using a combination of genomic and proteomic database searches and individual protein import assays. We show that Arabidopsis chloroplasts have at least 19 J proteins, the highest number of confirmed J proteins for any organelle. These 19 J proteins are classified into 11 clades, for which cyanobacteria and glaucophytes only have homologs for one clade, green algae have an additional three clades, and all the other 7 clades are specific to land plants. Each clade also possesses a clade-specific novel motif that is likely used to interact with different client proteins. Gene expression analyses indicate that most land plant-specific J proteins show highly variable expression in different tissues and are down regulated by low temperatures. These results show that duplication of chloroplast Hsp70 in land plants is accompanied by more than doubling of the number of its J protein cochaperones through adding new J proteins with novel motifs, not through duplications within existing families. These new J proteins likely recruit chloroplast Hsp70 to perform tissue specific functions related to biosynthesis rather than to stress resistance.